2005
DOI: 10.1007/s00276-005-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Does subthalamic nucleus stimulation affect the frontal limbic areas? A single-photon emission computed tomography study using a manual anatomical segmentation method

Abstract: Among the basal ganglia nuclei, the subthalamic nucleus (STN) is considered to play a major role in output modulation. The STN represents a relay of the motor cortico-basal ganglia-thalamo-cortical circuit and has become the standard surgical target for treating Parkinson's patients with long-term motor fluctuations and dyskinesia. But chronic bilateral stimulation of the STN produces cognitive effects. According to animal and clinical studies, the STN also appears to have direct or indirect connections with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Intraoperative fMRI imaging of PD patients during STN stimulation demonstrated simultaneous activation of limbic regions (cingulate and insular cortices) (Knight et al ., 2015). Similar studies using PET showed increased activation during STN stimulation in the dorsolateral prefrontal cortex bilaterally (Haegelen et al ., 2005) and the anterior cingulate (Sestini et al ., 2002). …”
Section: Stn Involvement In Limbic Functionsupporting
confidence: 67%
“…Intraoperative fMRI imaging of PD patients during STN stimulation demonstrated simultaneous activation of limbic regions (cingulate and insular cortices) (Knight et al ., 2015). Similar studies using PET showed increased activation during STN stimulation in the dorsolateral prefrontal cortex bilaterally (Haegelen et al ., 2005) and the anterior cingulate (Sestini et al ., 2002). …”
Section: Stn Involvement In Limbic Functionsupporting
confidence: 67%
“…Schroeder et al [41,42] reported decreased [26] observed decreased rCMb in the right orbitofrontal cortex, correlated with impaired recognition of fear. In a previous SPECT study, we observed activation in the dorsolateral prefrontal cortex bilaterally [20]. STN DBS may impair prefrontal functions via two different mechanisms, either the inhibitory effect of the stimulation on its limbic territory, or more probably, faulty transmission of cortical information to the substantia nigra pars reticulata and nucleus accumbens, structures located within the same limbic circuit as the STN.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the STN’s rich connections with the dorsolateral prefrontal cortex and limbic structures,[25, 26] stimulation of this area could alter cognition. Poor performance on measures of VF (related to mental flexibility in the frontal-striatal circuitry) is related to high frequency stimulation, with a beneficial effect during low frequency stimulation.…”
Section: Discussionmentioning
confidence: 99%